MiR-216b suppresses cell proliferation, migration, invasion, and epithelial–mesenchymal transition by regulating FOXM1 expression in human non-small cell lung cancer - Wang, Lidong (Onco Targets Ther, 2019)
Background/aims: MiR-216b and forkhead box M1 (FOXM1) were demonstrated to exert their biological effects on the development and progression of tumors. This study aimed to investigate the expression and role of miR-216b and FOXM1 in tissues and cell lines of non-small cell lung cancer (NSCLC). Methods: The expressions of miR-216b and FOXM1 in NSCLC tissues and cells were detected by qRT-PCR and Western blot analysis. Cell proliferation was measured by CCK-8 assay. Cell migration and invasion were confirmed by Transwell assay. Finally, the bioinformatics and dual-luciferase reporter assay were conducted to validate the relationship of miR-216b and FOXM1. Results: Compared with normal tissues and cells, the expression of miR-216b was obviously decreased in NSCLC tissues and cells. However, the expressions of FOXM1 mRNA and protein were significantly increased, and negatively correlated with the expression of miR-216b. Multivariate Cox’s regression analysis suggested that miR-216b or FOXM1 expression was an independent prognostic factor for patients with NSCLC. MiR-216b overexpression remarkably repressed cell proliferation, migration, invasion, and epithelial–mesenchymal transition (EMT) of NSCLC cells. The bioinformatics and dual-luciferase reporter assay validated that the 3ʹ-untranslated region (3ʹ-UTR) of FOXM1 mRNA was indeed a direct target of FOXM1. In vitro, overexpression of FOXM1 partially eliminated inhibitory effects of miR-216b on cell proliferation, migration, and invasion, whereas inhibition of FOXM1 contributed to inhibitory effects mediated by miR-216b. Conclusion: MiR-216b inhibits cell proliferation, migration, invasion, and EMT by targeting the expression of FOXM1 in human NSCLC. These findings suggested a potential therapeutic role of miR-216b in patients of NSCLC.